Portable water filter device - Azhar, Muhammad Irsyad Zufayri; Wan Fauzi, Wan Muhammad Syahmi (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Access to clean and safe drinking water remains a critical global challenge, especially in remote and disaster-stricken areas. Contaminated water sources pose severe health risks, leading to waterborne diseases that affect millions worldwide. To address this issue, this project focuses on the design and fabrication of a portable water filter device that provides a reliable, cost-effective, and user-friendly solution for water purification. The proposed device utilizes a multi-stage filtration system, including12V water pump, ceramic filtration and activated carbon to effectively remove impurities, bacteria, and harmful contaminants. The methodology involves material selection, prototype development, and performance testing under different water conditions to ensure optimal efficiency. The design emphasizes portability, durability, and ease of use, making it suitable for outdoor activities, emergency situations, and rural communities with limited access to clean water. The results demonstrate that the device able to improve water quality by reducing turbidity, eliminating harmful microorganisms, and removing odor and undesirable tastes. By offering an affordable and practical solution, this portable water filter device contributes to public health improvements, disaster relief efforts, and sustainable access to safe drinking water. Future advancements may incorporate additional purification technologies and smart monitoring features to enhance usability and efficiency.